2023
DOI: 10.1002/ijc.34462
|View full text |Cite
|
Sign up to set email alerts
|

Real‐world clinical outcome and safety of adjuvant therapy in stage III melanoma patients: Data from two Academic Italian Institutions

Abstract: Adjuvant immunotherapy (IO) and targeted therapy (TT) have improved relapse-free survival (RFS) in patients with stage III melanoma, although about 25% of them relapse within a year. However, real-world data on treatment efficacy and safety as well as management of treatment recurrences are still limited. We retrospectively analyzed 113 patients with stage III melanoma who received at least one cycle of anti-PD-1 (nivolumab or pembrolizumab) or dabrafenib + trametinib as adjuvant therapy. Most of patients incl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 21 publications
(41 reference statements)
1
3
0
Order By: Relevance
“…Subgroup analyses from two previous real-world study with smaller D/T sample size and shorter follow-up time comparing D/T to PD-1, regardless of stage and mutation status, showed that 1-yr RFS rate was 65–78% in the PD-1 group and 87–95% in the D/T group. 7 , 8 In this study we observed a similar 1-yr RFS rate (76% in the PD-1 group and 93% in the D/T group).…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Subgroup analyses from two previous real-world study with smaller D/T sample size and shorter follow-up time comparing D/T to PD-1, regardless of stage and mutation status, showed that 1-yr RFS rate was 65–78% in the PD-1 group and 87–95% in the D/T group. 7 , 8 In this study we observed a similar 1-yr RFS rate (76% in the PD-1 group and 93% in the D/T group).…”
Section: Discussionsupporting
confidence: 79%
“…BRAF / MEK inhibitors (dabrafenib/trametinib, D/T) and anti-PD-1 monotherapy (PD-1) have been approved as standard post-definitive surgery adjuvant therapies for stage III BRAF V600 mutant melanoma, based on large randomized control trials demonstrating prolonged relapse-free survival (RFS). 3 , 4 , 5 , 6 Although emerging real-world data 7 , 8 with short follow-up suggested that there might be RFS advantage of D/T over PD-1 at 12-month landmark, these were subgroup comparisons between D/T and PD-1 regardless of BRAF mutation status and melanoma stage and with no confounder adjustment. In addition, there is still a lack of direct comparison between recurrence pattern and toxicities, especially those with long-term impact (e.g., chronic hormone supplementation).…”
Section: Introductionmentioning
confidence: 99%
“…25 Similar to our study, real-world data from the Dutch and Italian groups also reported lower rates of severe AEs (11.5% and 17.2%) with adj TT. 26,27 However, both in our study and other real-world reports, including the Dutch study, discontinuation rates of adj TT were higher (41% and 29-39%) than the COMBI-AD trial (26%) or trials in the metastatic setting. 27,29 The discordance in low grade ≥3 AEs and high cessation rates due to toxicity is most likely due to less meticulous AE grading, as well as lower tolerance for AEs by both patients and practitioners, both of which are frequently seen in real-life practice.…”
Section: Discussioncontrasting
confidence: 56%
“…Strengths of this chart review study include the substantial number of patients with stage III melanoma from various practice settings across the US providing valuable real-world evidence of the management of resected melanoma in the US. Additionally, substage III data were used to identify factors associated with AT receipt among patients with stage IIIA disease and the drivers behind these choices; this had not been explored in previous real-world studies [ 21 , 26 ]. This study also used extensive information from different sources – a physician survey to describe their clinical practice experience and patient-level data obtained from chart review.…”
Section: Discussionmentioning
confidence: 99%